2013
DOI: 10.1080/1612197x.2013.830434
|View full text |Cite
|
Sign up to set email alerts
|

Measurement invariance of the Behavioural Regulation in Sport Questionnaire when completed by young athletes across five European countries

Abstract: The purpose of this study was to contribute to the factorial validity of the Behavioural Regulation Sport Questionnaire (BRSQ) by providing (1) an adaptation of the BRSQ to the young competitive athletes (YBRSQ) targeted in the PAPA project (i.e., 9-15 years old) in five European countries

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
0
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 28 publications
4
30
0
8
Order By: Relevance
“…Each item was rated on a 5-point Likert scale ranging from 1 (not true at all) to 5 (very true). Previous research lent credence to the validity and reliability of the French BRSQ scores (Van Hoye et al, 2010;Viladrich et al, 2013). Cronbach's alphas ranged from .60 to .87 (Table 1).…”
Section: Methodsmentioning
confidence: 57%
“…Each item was rated on a 5-point Likert scale ranging from 1 (not true at all) to 5 (very true). Previous research lent credence to the validity and reliability of the French BRSQ scores (Van Hoye et al, 2010;Viladrich et al, 2013). Cronbach's alphas ranged from .60 to .87 (Table 1).…”
Section: Methodsmentioning
confidence: 57%
“…In this study, we aimed to analyze BRSQ invariance across the gender and four different sports while also examining the nomological validity between BPNs' satisfaction and different forms of motivation. SDT constructs are assumed to be universal influences on human motivation , as also highlighted in other studies (e.g., Villadrich et al, 2013), since constructs underlying behavioral regulations have shown invariance across the gender (Lonsdale et al, 2008), competitive level (Hancox, Quested, Villadrich, & Duda, 2015), and cultural background (Villadrich et al, 2013). Consequently, and according to Stenling et al (2018) and Monteiro et al (2018), we hypothesised that the BRSQ would be invariant across the gender and across different sports.…”
Section: The Present Studymentioning
confidence: 74%
“…La motivación fue evaluada con la versión española del Cuestionario de Regulación Conductual en el Deporte (BRSQ-6; Lonsdale, Hodge y Rose, 2008) adaptada para jóvenes futbolistas (Viladrich et al, 2013). En esta escala que consta de 20 ítems, divididos en cinco subescalas, se les solicita a los futbolistas que indiquen en qué medida cada una de las razones expuestas explican por qué juegan al fútbol con su equipo.…”
Section: Instrumentosunclassified
“…Las respuestas se recogen en una escala tipo Likert que oscila desde (1) muy en desacuerdo a (5) muy de acuerdo. Investigaciones previas han con rmado la abilidad del instrumento (e.g., Lonsdale et al, 2008;Viladrich et al, 2013). Siguiendo el ejemplo de estudios previos (p.e., Balaguer, Castillo y Duda, 2008; Standage, Duda y Ntoumanis, 2003), para operacionalizar la motivación autodeterminada, se utilizó un índice de autodeterminación.…”
Section: Instrumentosunclassified